Analysis of the composition of culturable airborne microorganisms in the archaeological excavation protection site of the Nanhai No. 1 Ancient Shipwreck - Ma, Kaixuan; Wang, Yu; Yang, Xinyu; Wang, Cen; Han, Yeqing; Huang, Xinduo; Guo, Peifeng; Du, Jing; Chen, Yue; Pan, Jiao (Frontiers in Microbiology, 2022)
Microorganisms are important biological components in the air. The Nanhai No.1 was an ancient wooden shipwreck from the Chinese Southern Song Dynasty. After the overall recovery of the ship from the sea on 2007, the Nanhai No. 1 Ancient Shipwreck is currently exposed to the air. In addition, the hull timber needs to be sprayed and moisturized for conservation purposes. Since the air humidity is high, it can lead to the growth and proliferation of microorganisms on the hull. Therefore, the microorganisms can cause biocorrosion and biodegradation of the ship. In this study, a systematical survey of airborne microorganisms was performed at the conservation site of the Nanhai No. 1 Ancient Shipwreck. Air samples were taken from seven sites in the preservation Nanhai No.1 area. Airborne microorganisms were collected using a Zr- 2050 air sampler (Junray, China) in five times (April 2016, October 2016, June 2017, November 2019, and September 2020). Then, a molecular identification of the isolated airborne microorganisms was done by sequencing both 16S rRNA (bacteria) and ITS (fungi) gene regions. The dominant bacterial genus was Acinetobacter sp., and the dominant fungal genus was Penicillium sp., Aspergillus sp., and Cerrena sp. These dominant genera have been reported as potentially harmful microorganisms in the environment. The composition of the isolated microbial community had seasonal variations, and its spatial distribution was different. Airborne microbial communities are closely related to relative air humidity, temperature, rainfall, and human activities. This study provides comprehensive data on the airborne microbial community found at the protection site of the Nanhai No. 1 shipwreck, which can be used as an important reference basis for the future conservation of the ship.